Objection sustained: Anscombe's challenge to modern moral philosophy's use of the concept of obligation - Njoroge, John Mwangi (University of Georgia, 2018)
In this project, I clarify and expand on G.E.M. Anscombe's claim that it's logically incoherence for philosophers to employ the concept of obligation in their moral theories without acknowledging the existence of a lawgiving God. I refer to this critique of contemporary moral philosophy as "Anscombe's Challenge", designating it as "AC" for short. I argue that for AC to be successful, it needs to be shown both that a lawgiving agent is necessary to make sense of the concept of obligation and that human beings, individually or collectively, do not fully suffice as the appropriate lawgiving agents. In the bulk of the project, I examine three responses to AC. The first is the Divine Command Theory (DCT) which endorses AC and argues that AC is not a problem to philosophy since moral obligations are really God's commands, whether or not human beings recognize them as such. The second is the Social Command Theory (SCT) which acknowledges that moral obligation is agent-relative but argues that no supernatural agent is needed to account for it since obligations arise from within human societies. The final one is a form of naturalism that casts obligation in an agent-neutral way: moral obligations exist necessarily and they therefore don't need an agent to account for them. I argue that SCT must deny the objectivity of moral obligation, thus making obligations relative to society. By denying that moral obligation is agent-relative, naturalists concede Anscombe's point that obligation should not be understood in terms of the commanded. DCT defenders argue that, by giving up on objectivity (SCT) and the agency behind obligation (naturalists), both SCT and naturalism fail to account adequately for the law-like force of obligation and for the intrinsic worth of humanity. DCT claims to be able to account for both features of morality since God is seen as the source of the commands behind human obligations who also maintains a unique relationship with human beings as their Creator, thus conferring them intrinsic worth. I conclude each section with an examination of what I take to be the best arguments against each view
free